Pengembangan Produk Olesan Menggunakan Oleogel Minyak Sawit Merah sebagai Pensubstitusi Lemak Padat - Rachmawati, Annisa Noor; Wulandari, Nur; Purnomo, Eko Hari (Jurnal Teknologi dan Industri Pangan, 2024)
Red palm oil (RPO) is a derivative product of crude palm oil rich in carotenoids, which can be developed into food products as a source of provitamin A. Although RPO is liquid at room temperature, it is often applied in the form of solid fat, generally through the addition of solid fat fractions containing a large quantity of saturated fatty acids. Therefore, RPO must be modified to turn it into solid at room temperature without changing its fatty acid composition, resulting in RPO oleogel. This study aimed to obtain a spread product formula using RPO oleogel made with beeswax oleogelator to substitute stearin and to characterize the quality of the spread product. The research consisted of two main stages, namely formulation and characterization of RPO oleogel and spread product samples. As a result, oleogelation increased the RPO resistance to temperature changes. Moreover, RPO slip melting point increased from 16.33±0.58–18.00±0.00 to 38.00±0.00–39.33±0.58 °C when it became RPO oleogel. RPO oleogel, which is substituted in spread products, produced higher total carotenoids and spreadability compared to spread products with stearin as a raw material. The hedonic sensory test showed that the most preferred product was 60% RPO oleogel substitution, resulting in spreadability of 285.0±0.6 mm/min, despite not significantly different from commercial one (257.4±3.0 mm/min) and carotenoid content of 462.93±10.32 ppm. However, the taste attribute of the selected spread product still needs to be improved (acceptance score 3.65±1.31 from a maximum score of 7).